The normative reasons of "sacrifice" in revealed ethics - Mohammad Amin Khansari (اخلاق وحیانی, 2024)
Social upbringing of children, especially in face-to-face interaction, is one of the expectations that has been taken into consideration in different ways in Islamic teachings. The basic question is, what are the benefits of social education of children, especially in face-to-face interaction with others, and what are the most important effects of social education focused on face-to-face interaction? This article analyzes and explains the benefits of social education of children with the descriptive-analytical processing method, and especially explains the effects of social education that focuses on face-to-face interaction. By reflecting on Quranic and hadith teachings, it can be claimed that social education of society members and especially children is a social necessity and one of the important duties of parents is social education of children. Social education of children, especially in relation to face-to-face interaction with members of the society, facilitates social relations, increases social capital, increases the sense of empathy and intimacy, improves social status, increases mutual trust and reduces socio-cultural conflicts.